1998
DOI: 10.1101/gad.12.20.3217
|View full text |Cite
|
Sign up to set email alerts
|

WT1 interacts with the splicing factor U2AF65 in an isoform-dependent manner and can be incorporated into spliceosomes

Abstract: WT1 is essential for normal kidney development, and genetic alterations are associated with Wilms' tumor, Denys Drash (DDS), and Frasier syndromes. Although generally considered a transcription factor this study has revealed that WT1 interacts with an essential splicing factor, U2AF65, and associates with the splicing machinery. WT1 is alternatively spliced and isoforms that include three amino acids, KTS, show stronger interaction with U2AF65 in vitro and better colocalization with splicing factors in vivo. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
170
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(179 citation statements)
references
References 39 publications
8
170
1
Order By: Relevance
“…Alternatively, WT1 ( þ Ex5/ þ KTS) could affect which E-cadherin splice forms are expressed. This isoform of WT1 has been implicated in regulation of alternative splicing (Davies et al, 1998), and perhaps this activity is responsible for the observed effect on E-cadherin localization. This would be consistent with a lack of effect of WT1 (ÀEx5/ÀKTS), which has not been implicated in the regulation of mRNA splicing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, WT1 ( þ Ex5/ þ KTS) could affect which E-cadherin splice forms are expressed. This isoform of WT1 has been implicated in regulation of alternative splicing (Davies et al, 1998), and perhaps this activity is responsible for the observed effect on E-cadherin localization. This would be consistent with a lack of effect of WT1 (ÀEx5/ÀKTS), which has not been implicated in the regulation of mRNA splicing.…”
Section: Discussionmentioning
confidence: 99%
“…The other alternative splice involves the use of one of the two distinct splice acceptor sites at the N-terminus of exon 10, resulting in the inclusion of three additional amino acids (KTS) in the larger protein isoform, altering the spacing of the zinc-fingers that compose the DNA-binding domain. The presence or absence of this so-called KTS insert has profound functional consequences for the mature protein, affecting both DNA-binding and subcellular localization, but the functional importance of exon 5 remains unclear (Larsson et al, 1995;Davies et al, 1998;Natoli et al, 2002;Reynolds et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…3,[10][11][12] At least 36 isoforms of WT1 protein are produced from the same DNA template as a result of alternative transcription initiation, alternative pre-mRNA splicing, mRNA editing and alternative translation initiation. 1,3,5,10,[13][14][15][16][17][18] The four major WT1 isoforms are generated by an alternative splicing and vary in the presence or absence of so called 17AA insert (17 amino acids encoded by the whole exon 5) and KTS insert (according to the three amino acids leucinethreonine-serine encoded by the terminal sequence of exon 9)- [19][20][21][22][23] An alternative WT1 transcript, AWT1 (also short transcript, sWT1), maintains WT1 exonic structure between exons 2 and 10 but uses another first exon located in intron 1 of WT1 (exon 1a). It may otherwise exist in all splicing variants characteristic of WT1.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent reports have shown evidence that WT1 is involved not only in transcriptional regulation in the nucleus but also in RNA metabolism and translational regulation in the cytoplasm. The binding of WT1 to splicing factors 25 and murine IGF-II mRNA 26 in vitro was demonstrated. Furthermore, nucleocytoplasmic shuttling of WT1 and the association of WT1 with actively translating polysomes were reported.…”
mentioning
confidence: 99%